Analysis of Cetyl Pyridinium Chloride (CPC) by Raman Spectroscopy Method - Yadav, Chandradip Kumar; Maharjan, Jasana; Rakesh, Benedict; Bhattarai, Ajaya (Amrit Journal, 2024)
Surface active agents (surfactants) have found various critical technological applications, from helping infant lungs breathe to fugitive dust control at industrial sites. Surfactant molecules adsorb to an interface and facilitate a decrease in the surface free energy (interfacial tension) between two immiscible phases. However, a limited number of methods (e.g., holography and fluorescence microscopy) achieved qualitative visualization of surfactant molecule distribution in multiphase systems. To probe the efficacy and/or adsorption density of surfactants at such interfaces quantitatively, we demonstrate here a direct observation of surfactant adsorption by Surface-Enhanced Raman Scattering (SERS). This work details the development of a research platform to study surfactant adsorption using Raman imaging. The imaging and analysis were successfully benchmarked against conventional interfacial tension measurements and thermodynamic theory employed to estimate surfactant adsorption at equilibrium. This in situ Raman-based experimental method provides a platform to interrogate structure-function relationships that inform the design process for new surfactant species.